The influence of integrative lighting on sleep and cognitive functioning of shift workers during the morning shift in an assembly plant. (February 2022) - Van de Putte, Eowyn; Kindt, Sara; Bracke, Peter; Stevens, Michael; Vansteenkiste, Maarten; Vandevivere, Lore; Ryckaert, Wouter R.
Abstract: It is well known that exposure to light at the right time of the day is important to synchronise our circadian rhythm and enhance cognitive functioning. There is, however, a lack of field studies investigating which lighting characteristics are necessary to improve sleep and cognitive functioning. A controlled field study with 80 shift workers was set up, in which the impact of an integrative lighting (IL) scenario was investigated during the morning shift. Two groups were compared: a control group (no change in lighting settings) and a IL-group (exposed to a melanopic Equivalent Daylight Illuminance of 192 lux, i.e., bright light with a high fraction of short-wavelengths). Pre-post measurement of visual comfort, cognitive functioning (D2 task, go-nogo reaction time task) and sleep (MotionWatch8) were performed. The IL-settings ameliorated sleep efficiency and sleep latency during morning shift and enhanced alertness (not inhibition) compared to standard lighting conditions. Changing lighting settings in an industrial setting should be considered as it seems worthwhile for employees' sleep and cognitive performance. Highlights: In an industrial setting 192 lux melanopic Equivalent Daylight Illuminance (melanopic EDI) is sufficient to enhance employees' sleep and cognitive functioning. Integrative lighting improves shift workers' sleep and attention.